Identification and Explanation of the Dimensions, Components, and Indicators of Human Resource Governance Based on National Culture in the Public Sector of Kerman City - Karimi Afshar , Samaneh; Sharafi, Shahin; Ranjbar, Mokhtar; Salajeghe, Sanjar; Nikpour, Amin (Management Strategies and Engineering Sciences, 2024)
The aim of this research is to identify the dimensions, components, and indicators of human resource governance based on national culture in the public sector of Kerman city. The research method, in terms of its goal, is fundamental-applied, and in terms of execution, it is qualitative, descriptive, and thematic analysis. The statistical population of this study, based on the saturation principle, included 30 university professors, experts, and human resource managers from the executive agencies in the public sector of Kerman city. They were selected using purposeful and snowball sampling methods, based on the inclusion criteria for the study. The data collection tool was semi-structured interviews. The data were analyzed using MAXQDA2020 software and the six-phase thematic analysis approach by Braun and Clarke (2006). To evaluate the validity and rigor of the data, four criteria—acceptability, reliability, transferability, and confirmability—proposed by Lincoln and Guba were applied. Based on the semi-structured interviews, seven dimensions (talent management, human resource development, employee well-being and welfare, integrated human resource policies, human resource roles and responsibilities, human resource risk management, and national culture [Iranian-Islamic]) were identified, along with 22 components (organizing themes) and 78 indicators (basic themes). The results of this research can serve as a practical guide for human resource managers in this area. Furthermore, the contribution of this study to knowledge and its practical application can be found in its focus on the conditions for implementing human resource governance at the national level with an institutional perspective.